2018
DOI: 10.1186/s12913-018-3361-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and mortality of emergency department patients in the North Denmark region

Abstract: BackgroundEmergency departments handle a large proportion of acute patients. In 2007, it was recommended centralizing the Danish healthcare system and establishing emergency departments as the main common entrance for emergency patients. Since this reorganization, few studies describing the emergency patient population in this new setting have been carried out and none describing diagnoses and mortality. Hence, we aimed to investigate diagnoses and 1- and 30-day mortality of patients in the emergency departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 17 publications
2
28
1
1
Order By: Relevance
“…Several studies found that non-specific diagnoses represent a considerable part among acute patients: among patients taken to hospital by ambulance after calling 112 [3], among acute medical admissions [9,10] and among all patients with contact to emergency departments [11].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found that non-specific diagnoses represent a considerable part among acute patients: among patients taken to hospital by ambulance after calling 112 [3], among acute medical admissions [9,10] and among all patients with contact to emergency departments [11].…”
Section: Discussionmentioning
confidence: 99%
“…Emergency calls to EMS display a diurnal pattern with the highest number of call occurring during daytime [23] and differences in proportion of certain diseases and admission rates between daytime and OOH in primary care have also been reported [33][34][35]. Nevertheless, Vest-Hansen et al [36] reported circulatory disease (19.3%), other factors (16.9%), infections (15.5%), symptoms and signs (11.8%) and injury and poisoning (6.3%) as the top five ICD-10 chapters used in acute admissions to a medical ward (not including surgical specialties, which explains the lower proportion of injuries and poisoning) and a study on emergency department contacts found injuries and poisoning (38.3%), symptoms and signs (16.1%), other factors (14.5%), circulatory diseases (5.7%) and respiratory diseases (5.4%) as the most frequent chapters [37]. These studies did not investigate whether the patients arrived at hospital after calling EMS or OOH-PC.…”
Section: Comparison With Literaturementioning
confidence: 99%
“…Acute dyspnoea is a distressing symptom with a sensation of difficult, laboured and uncomfortable breathing [1,2]. It is the symptom of numerous acute as well as chronic diseases, and it is a frequent symptom seen among patients in the emergency departments as well as in the ambulances [3,4]. A study of emergency medical service patients from the United States of America showed that in 2002-2006, one in eight of the patients had respiratory distress, when excluding traumatic injury and cardiac arrest [5].…”
Section: Introductionmentioning
confidence: 99%